Environmental & architectural phenomenology. Vol.22, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 2011)
Vol. 22, No. 1, Winter 2011 (includes “items of interest” and essays by Paul Krafel, Christine Rhone, Jeremy Wells, & Reza Shirazi).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals